Triangulated perspectives on outcomes of pulmonary rehabilitation in patients with COPD: a qualitative study to inform a core outcome set - Souto-Miranda, Sara (2019)
Pulmonary rehabilitation implies a comprehensive assessment. Although several outcomes are commonly measured, those are selected mainly by health professionals and researchers, with the voice of patients and informal caregivers being minimally captured. Qualitative studies are fundamental to enhance our knowledge on perspectives of different stakeholders involved in pulmonary rehabilitation.